1, 2, 4-Triazolium perfluorobutanesulfonate as an archetypal pure protic organic ionic plastic crystal electrolyte for all-solid-state fuel cells12. Issue 4 (1st April 2015) - Luo, Jiangshui; Jensen, Annemette H.; Brooks, Neil R.; Sniekers, Jeroen; Knipper, Martin; Aili, David; Li, Qingfeng; Vanroy, Bram; Wübbenhorst, Michael; Yan, Feng; Van Meervelt, Luc; Shao, Zhigang; et al.
<x xml:space="preserve">Abstract</x> Protic organic ionic plastic crystals (POIPCs) are shown to be novel anhydrous solid-state proton conductors for fuel cells.